Velocity versus Offset (VVO) Estimation Using Local Event Correlation and Its Application in Seismic Processing & Analysis - S. Supriyono; Awali Priyono; Wahyu Triyoso; Hilman Mardiyan (Journal of Engineering and Technological Sciences, 2013)
Conventional velocity analysis is usually done in a relatively spare grid, for instance every half kilometers, during the processing of seismic data. It is very laborious work and very subjective. To deliver an accurate velocity picking, processing geophysicists must have a good understanding of geological background of area being analyzed and experiences. Velocity errors often occur during picking. Proper quality control and checking are a must. A good and reliable velocity field is very important in seismic processing for achieving high-quality seismic images as well as for delivering an accurate depth conversion. The new method presented here, was developed to correct velocity errors automatically by means of residual velocity correction, and to produce an offset-dependent RMS velocity field at the same time. The method is data driven, based on the normal move out equation (NMO) and measuring the local even correlation between adjacent traces. The stacking velocity is derived simply by averaging the velocity field. The proposed method was tested on synthetic and real data examples with good result. The velocity field has certain characteristics related to hydrocarbon presence. Supriyono (2011 and 2012) developed a new DHI method using velocity gradient attributes by cross-plotting the velocity versus offset (VVO). The velocity gradient exhibits high anomalous values in the presence of gas.